DEVELOPMENT OF STEM EDUCATION INTEGRATED SOUND AND LIGHT WAVES E-MODULE FOR CRITICAL AND CREATIVE THINKING SKILLS OF HIGH SCHOOL STUDENTS - Nadila Fathiya; Asrizal Asrizal (Universitas Negeri Padang, 2022)
21st-century education is an education described by the utilization of computerized innovation in the educational experience to further develop student's critical and creative thinking skills. The integrated teaching module of STEM education is still low, this is obtained from the analysis of STEM integration in textbooks, which is 57.89. The answer for defeat these issues is to foster a coordinated sound wave and light wave e-module in STEM schooling. This study aims to reveal the validity of the integrated sound wave and light wave e-module in STEM education. This type of research is included in research and development. This study uses the ADDIE development model. The instrument in this study used a content validity sheet. Technical analysis of the data in this study using Aiken's V. In view of the outcomes of the analysis of Aiken's V obtained a value of 0.83. Product validity is interpreted as a high validity category because the score is 0.8. In view of the aftereffects of this review, it was inferred that the e-module of sound waves and light waves integrated with STEM education was in the valid category and could be used in learning in schools on aspects of material substance, visual communication display, instructional design, software usage, and STEM assessment. Researchers hope that this e-module can be a reference for technology-based learning resources to create meaningful learning to encourage the improvement of high school students critical and creative thinking skills.